Management of a Mediterranean Forage/Cereal-Based Cropping System: An Ecosystem Service Multisectoral Analysis in the Perspective of Climate Change - Matteo Francioni; Laura Trozzo; Nora Baldoni; Marco Toderi; Marco Bianchini; Ayaka Wenhong Kishimoto-Mo; Paride D’Ottavio (Atmosphere, 2022)
Within Mediterranean cropping systems, legume forage crops that last up to 6 years or more (e.g., alfalfa) are replaced with cereal crops (e.g., wheat). The change from forage to cereal crops has negative climate and environmental impacts that must be addressed with mitigation actions. This study evaluated the synergies and tradeoffs between the ecosystem services provided by three management systems after forage legume. A field trial was set up from October 2017 to September 2019 on a 6-year-old alfalfa field subjected to the following management systems: (i) alfalfa termination followed by wheat for 2 years (WW, control); (ii) alfalfa termination followed by single amendment with 60 Mg ha−1 recalcitrant biochar and then by wheat for 2 years (WWB60); and (iii) extension of alfalfa for 2 years (AEXT). A range of regulating, supporting, and provisioning ecosystem services were assessed during the 2018 and 2019 cropping seasons. The results highlight that WWB60 can guarantee carbon sequestration without causing tradeoffs with other services, while AEXT can enhance soil conservation while not increasing soil greenhouse gas emissions. Future policies should support the WWB60 system if the goal is to increase the supporting services. Conversely, the AEXT system should be used if the goal is to increase the regulating and provisioning services.